Introducción y antecedentes - Rodríguez, Sergio (Coloquios de Paleontología, 1992)
The Los Santos de Maimona basin is located in the Badajoz Provinee. Sierra Mcrena. 5W Spain. It is 12km long, 1 to 3km wide, aid contains very varied rock (carbonate. siliciclastie ancí volcanie). ibis basin is included in the Ossa-Morena stritctural zone. and it is beunded Uy tear faults having a NW-SE direction. It has been studied since the Iast century. The ocurre'nce of fossiliferous limestones wasfirsl reponed Uy GONZA LO ylARIN (1879). In spite of the paleontological interest inthese limestones. onlysomegeneral straíigraphicworks(NAVARRO& i..ACAZIEFIE. 1922, RUSSO DEI ~UNA HERNANDEZ-PACIIECO. 1955; LAUS. 1968) and partial & paleontt>Iogical reports (JONGMANS. 1956; ALTEVOGT, 1966) were published on the'tn unlil 1983. In thai year, the aehievement el the National Geologie Map (1: 50.000) of ¡he Sierra Morena Regicn activated studies on this area (ODRIOZOLA e/aL, 1983; QUESADA. 1983; WAGNER e/al. 1983k (jABALDON el aL, 1985). A detailled study en Ihe st raligraph y and pa Ieontology c)f th is basi n was begu n iii 1987 Uy two diñe rent groups of (he Madrid ancl Badajoz Universities. Sorne results of these studies were published duning recent years (SANCI-IEZetaL, 1988,199k PALACIOS GONZALEZ ci aL, 199(1: RODRíGUEZ & COMAS-RENGIFO, 990; VAl ENZUL! A el aL, 199<); SOI.ER-G!jON & RODRIC;UEZ, 1991, ROI)RIGUEZ el al. in press).